2015
DOI: 10.1105/tpc.114.135996
|View full text |Cite
|
Sign up to set email alerts
|

DENEDDYLASE1 Deconjugates NEDD8 from Non-Cullin Protein Substrates in Arabidopsis thaliana

Abstract: The evolutionarily conserved 8-kD protein NEDD8 (NEURAL PRECURSOR CELL EXPRESSED, DEVELOPMENTALLY DOWN-REGULATED8) belongs to the family of ubiquitin-like modifiers. Like ubiquitin, NEDD8 is conjugated to and deconjugated from target proteins. Many targets and functions of ubiquitylation have been described; by contrast, few targets of NEDD8 have been identified. In plants as well as in non-plant organisms, the cullin subunits of cullin-RING E3 ligases are NEDD8 conjugates with a demonstrated functional role f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 63 publications
7
46
0
Order By: Relevance
“…Our previous comparative analyses of den1 and csn5 mutants from Arabidopsis thaliana showed that, at least in Arabidopsis, DEN1 is specifically required to remove NEDD8 from neddylated substrates other than cullins (31). We further identified AXR1 and, indirectly, also the paralogous AXL as prominent NEDD8-modified proteins that depend on DEN1 for deneddylation (31).…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…Our previous comparative analyses of den1 and csn5 mutants from Arabidopsis thaliana showed that, at least in Arabidopsis, DEN1 is specifically required to remove NEDD8 from neddylated substrates other than cullins (31). We further identified AXR1 and, indirectly, also the paralogous AXL as prominent NEDD8-modified proteins that depend on DEN1 for deneddylation (31).…”
mentioning
confidence: 73%
“…We further identified AXR1 and, indirectly, also the paralogous AXL as prominent NEDD8-modified proteins that depend on DEN1 for deneddylation (31). AXR1 and AXL share ϳ80% amino acid identity, and both can form a complex with ECR1 (E1 C-TERMINAL RELATED1) (23,32).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…For instance, because USP2cc recognizes the last five amino acids of ubiquitin and no other ubiquitin-like proteins harbor this sequence at their C termini, this DUB is ubiquitin specific in plants, in contrast to the K-e-GG antibodies that also recognize the epitope generated upon tryptic cleavage of other small protein modifiers, such as RELATED TO UBIQUITIN (Vierstra, 2012). Currently, it is difficult to assess to which extent this ambiguity is problematic because the degree of rubbylation in plants is unknown, but its functionality has been suggested to supersede that of neddylation, its mammalian PTM counterpart (Hakenjos et al, 2011;Mergner and Schwechheimer, 2014;Mergner et al, 2015).…”
Section: Outlook We Are Ready For "Site"-seeing In Plantsmentioning
confidence: 95%